Low-temperature complete combustion of a dilute mixture of methane and propane over transition-metal-doped ZrO2 catalysts: effect of the presence of propane on methane combustion - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Environmental Science and Technology, 2005)
Complete combustion of dilute methane alone or a dilute mixture of methane and propane over transition-metal (viz. Mn, Co, Cr, Fe, and Ni)-doped ZrO2 (cubic) catalysts at different temperatures (523-873 K) and a space velocity of 51 000 CM3 center dot g(-1)center dot h(-1) has been investigated for controlling methane and propane emissions from exhaust gases. The catalysts are compared for their catalytic ignition temperature and activity in the combustion of propane and methane in the presence of each other. The methane combustion activity of all the catalysts is strongly influenced by the presence of propane; it is decreased markedly. In the combustion of mixed methane and propane the Mn-doped ZrO2 and Cr-doped ZrO2 catalysts show the highest activity in the combustion of methane and propane, respectively; the Ni-doped ZrO2 shows the lowest activity in both cases. In the combustion of mixed methane and propane the propane combustion is enhanced but the methane combustion retarded when the Cr-doped ZrO2 and Mn-doped ZrO2 catalysts in a 1:1 ratio are used together in different ways (mixed or in layers).